EFEK KETIDAK COCOKAN SOSIAL ANTARA STAF AUDIT DAN MANAJEMEN KLIEN DALAM PROSES PENGUMPULAN BUKTI AUDIT (Studi Empiris pada Staf Audit KAP dan BPKP) - Hadjar Annisya; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This research was aimed to analyze the effect of social mismatch between staff auditors and client management on the collection of audit evidence which may affect audit quality. This research is a replication of the research that has been done by Bennet and Hatfield (2012) in USA, with different location, object, sample and analyzed method.Totally 90 samples of audit staff level in KAP and BPKP was used in this research. Data analysis method that has been used is non parametric test of Mann Whitney with SPSS 20 statistic program. The surveys’ results showed that most of audit staff level prefer to ask for the audit evidence via email than via personal meeting with management client, even though it doesn’t significant by statistic. Email could reduce the effect of social mismatch such as the high tone. But, personal meeting could reduce misinterpretations data by staff auditors.In general, we could conclude that social mismatch between staff auditors and client management on the collection of audit evidence did not affect staff auditors’ perception to ask for additional audit evidence from various kind of client management and email could be one of the alternative methods to ask for the additional audit evidences from client management.